Особливості євроінтеграційних процесів у сільськогосподарській сфері та сучасні соціально-економічні тенденції і криміногенні загрози в українському суспільстві: регіональний та загальнодержавний аспекти - Безпалько, С. В.; Bezpalko, S. V.; Шатрава, С. О.; Shatrava, S. O.; Тимчишин, А. М.; Tymchyshyn, A. M.; Кріцак, І. В.; Kritsak, I. V.; Іван Кріцак (Юридичний науковий електронний журнал. - 2022. - № 1. - С. 14-19, 2022)
Узагальнено глобальні виклики та загрози основному багатству України – землі. Виявлено криміногенні фактори соціально-економічних процесів сучасного соціуму. Особливу увагу акцентовано на цифровізації економіки. Передбачено майбутні тенденції переселення народів із міст до сільської місцевості в разі загроз об’єктам критичної інфраструктури. Наголошено на проблемах і перспективах розвитку міста, надано пропозиції подолання злочинності в містах. Зазначено, що правове регулювання економіки особливо впливає на політичні процеси держави і визначає, які партійні платформи займуть місце в наступних виборчих перегонах. Нинішній електорат може побоюватись посилення покарання за корупційно-злочинні схеми, що спричинить прихід до влади опозиції з регіоналістсько-радикальними настроями політичних сил та ідеології. Постійна політика розкрадання економічних ресурсів за таких умов стане неможливою. Визнано, що традиційні форми господарювання стають нерентабельними. Важливими є розроблення та впровадження ефективних управлінських рішень у різних галузях народного господарства.

In the article on the basis of an interdisciplinary method of scientific research an attempt is made to generalize global challenges and threats to the main wealth of Ukraine – the earth. Criminogenic factors of socio-economic processes of modern society are revealed. Particular attention accended on the digitalization of the economy. Future trends of relocation of folks from urban to rural areas in case of threats to critical infrastructure are foreseen. Is emphasized on the problems and prospects of the city development suggestions are attached for overcoming crime in cities. Except this, it is emphasized that the legal regulation of the economy especially aggects on the political processes of the state and determines which party platforms will take place in the next election derby. The current electorate may fear an increasing punishment for corrupt and criminal schemes, which will lead to the coming to power of the opposition with regionalist-radical sentiments of political forces and ideology. Continual policy of embezzling economic resources, under such circumstances, will become impossible. On the other side, it is emphasized that radical transformations of all spheres of social life are possible provided stable economy, taking into account the possibilities of total informatization and unprofitable. As we can see, traditional forms of management are becoming farms. Large transcorporations are created, which give the opportunity for a significantly increase the efficiency of various types of production, technologies, equipment. Under such conditions, it is important to develop and implement effective management decisions in various sectors of the national economy.

Обобщены глобальные вызовы и угрозы основному богатству Украины – земле. Выявлены криминогенные факторы социально-экономических процессов современного социума. Особое внимание акцентировано на цифровизации экономики. Предусмотрены будущие тенденции переселения народов из городов в сельскую местность в случае угроз объектам критической инфраструктуры. Отмечены проблемы и перспективы развития города, предоставлены предложения преодоления преступности в городах. Отмечено, что правовое регулирование экономики особенно влияет на политические процессы государства и определяет, какие партийные платформы займут место в следующей избирательной гонке. Нынешний электорат может опасаться усиления наказания за коррупционно-преступные схемы, что повлечет за собой приход к власти оппозиции с регионалистско-радикальными настроениями политических сил и идеологии. Постоянная политика хищения экономических ресурсов в таких условиях станет невозможной. Признано, что традиционные формы становятся нерентабельными. Важны разработка и внедрение эффективных управленческих решений в различных отраслях народного хозяйства.
Specifics of european integration processes in agricultural sphere and modern socio-economic trends and criminal threats in Ukrainian society: regional and national aspects
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Земельне право. Аграрне право. Land Law. Agrarian Law. Земельное право. Аграрное право; євроінтеграційні процеси; European integration processes; евроинтеграционные процессы; Кримінологія. Criminology. Криминология; економічна криза; economic crisis; экономический кризис; сільське господарство; agriculture; сельское хозяйство; соціально-економічні фактори; socio-economic factors; социально-экономические факторы; криміногенні виклики; criminogenic challenges; криминогенные вызовы; цифровізація; digitization; цифровизация; суспільство; society; общество; держава; правове регулювання; legal regulation; правовое регулирование; загальнодержавний аспект